2016
DOI: 10.14742/ajet.2830
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Graduate Students’ Reflection in E-portfolios Using the TPACK Framework

Abstract: When electronic portfolios (e-portfolios) are employed as summative assessments for degree granting programs, it is imperative that graduate students demonstrate their knowledge in the field to showcase learning growth and achievement of the program learning outcomes. This study examined the extent master's degree students in the field of educational technology demonstrated their technological pedagogical content knowledge (TPACK) related elements in their e-portfolio reflection, when they were guided by TPACK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The respondents referred to concrete examples of how technology can be used across various subject domains (cf. Ching, Yang, Baek, & Baldwin, 2016;Authors, 2015). Modeling technology integration activities would enhance pre-service teachers' repertoire of possible strategies they could use in their future classrooms (Chai, Koh, Tsai, & Tan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The respondents referred to concrete examples of how technology can be used across various subject domains (cf. Ching, Yang, Baek, & Baldwin, 2016;Authors, 2015). Modeling technology integration activities would enhance pre-service teachers' repertoire of possible strategies they could use in their future classrooms (Chai, Koh, Tsai, & Tan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The second SQD-strategy (Reflection) involves discussing and reflecting about the opportunities and the risks of ICT uses in education (Ching, Yang, Baek & Baldwin, 2016). This can help them see the values and /or risks of using a ICT in relation to a teaching and learning approaches (see Mouza et al, 2017).…”
Section: Figmentioning
confidence: 99%
“…This study found that students' poor knowledge of school level mathematics such as factorisation of a quadratic expression or decomposition of an irreducible quadratic led to them making errors in this problem. Understanding student's thinking in solving a mathematical problem contribute immensely in understanding their underlying challenges (Ching et al, 2016;Hunt & Little, 2019). Hence there is a need for instructors to learn more about the underlying challenges experienced by students.…”
Section: Discussionmentioning
confidence: 99%